Lost in translation? cultural adaptation of treatment content for Japanese internet-based cognitive therapy for social anxiety disorder - Yosinaga, N; Thew, G; Kobori, O; Hayashi, Y; Clark, D (Elsevier, 2021)
Studies that look to disseminate psychological therapies in different countries often discuss whether and how much cultural adaptation may be required. However, most do not provide sufficient descriptions of how language translation and cultural adaptations were performed, and rarely give examples of specific changes. This makes it hard to understand how much the adapted treatment differs from the original, causing difficulty when comparing studies. This study aimed to describe the translation and cultural adaptation process used to generate a Japanese version of a UK-developed online psychological therapy for social anxiety. It aimed to evaluate the translated and adapted content with a case series of Japanese patients. Following translation and back-translation, incorporating cultural adaptations where appropriate, the new Japanese content was reviewed and a list of adaptations collated and categorised. The Japanese treatment material was then evaluated using a guided self-study approach with six Japanese patients with social anxiety. Four categories of adaptation were identified: Linguistics and Metaphors, Social Systems, Social Behaviours, and Familiarity. Assigning instances of adaptation into these categories showed good interrater reliability (0.78). The Japanese materials showed excellent treatment efficacy (pre-post Hedges’ g=2.31). Patient feedback highlighted areas of strength, and further suggestions to improve suitability for Japanese settings. The clinical outcomes observed suggest that the translation and adaptation procedures were effective. Ways of further improving the adaptation based on patient feedback were identified. It is hoped that the translation procedure and adaptation categories described in this study may help other clinicians/researchers working to disseminate online psychological therapies crossculturally.